Pesticide exposure and cardiovascular health in non-CVD mortality population: novel evidence from NHANES 2007–2018 using Life's Essential 8 - Jiang He; Hexilin Wang; Xia Li (Frontiers in Nutrition, 2025)
BackgroundWhile pesticide exposure has become a global public health concern, its impact on cardiovascular health among non-cardiovascular mortality populations remains understudied.MethodsBased on NHANES 2007–2018 data (n = 12,432), we examined associations between five pesticide biomarkers (2,4-D herbicides, atrazine metabolites, organophosphate dimethyl and diethyl metabolites, glyphosate) and cardiovascular health, assessed by Life's Essential 8 (LE8) scores and Cardiometabolic Index (CMI). The associations were explored through multiple regression analyses, weighted quantile sum (WQS) regression, restricted cubic spline (RCS) analysis, and mediation analysis.Results2,4-D herbicides showed significant negative correlations with multiple LE8 components, particularly in BMI scores (β = −1.441, 95% CI: −2.158, −0.725) and diet scores (β = −1.241, 95% CI: −1.825, −0.658). Organophosphate metabolites demonstrated positive associations with smoking and diet scores. Dose-response analysis revealed an inverted U-shaped relationship between 2,4-D and LE8 scores, while organophosphates showed consistent positive correlations. WQS regression indicated that glyphosate contributed most significantly to LE8 scores (58%), while organophosphate diethyl metabolites dominated CMI effects (62%). Inflammatory markers (CRP and SII) played crucial roles in mediating pesticide exposure's effects on cardiovascular health.ConclusionThis study provides the first systematic evidence of association patterns between pesticide exposure and cardiovascular health in the general population, revealing differential impacts across pesticide types. These findings provide important scientific basis for understanding pesticide exposure's health effects and developing targeted prevention strategies.